God-Perfecting Man: Theurgical Elements in the Mysticism of Muḥyī l-Dīn Ibn al-ʿArabī (560/1165–638/1240) and Their Historical Significance - Michael Ebstein (Religions)
The following article aims at highlighting the theurgical tendencies in the teachings of the great Andalusī Muslim mystic Muḥyī l-Dīn Ibn al-ʿArabī (560/1165–638/1240). By “theurgy” is meant the influence of man on Divinity in its manifest external dimension, that is to say, the dimension of God that creates beings and is involved with their lives and fortunes, as opposed to His hidden essence. The category “theurgy/theurgical” is adopted from the modern academic study of Kabbalah, and is ultimately derived from Late Antique Neoplatonism. The bulk of this article is dedicated to analyzing relevant texts from Ibn al-ʿArabī’s oeuvre and elucidating the theurgical elements reflected in them, while the last two sections (5–6) present preliminary observations on the relevant links between Ibn al-ʿArabī, Kabbalah, and Late Antique Neoplatonism. It is argued that these three traditions should be studied together, as they shed light on one another.